2019
DOI: 10.26458/1913
|View full text |Cite
|
Sign up to set email alerts
|

Improving Tax Administration Through Technology Innovation in Nigeria (A Study of Federal Inland Revenue Service)

Abstract: This study investigates the impact of technology innovation on tax administration in Nigeria. Primary Data were collected through the use of structured questionnaire administered on 219 staffers of Federal Inland Revenue Service (FIRS) to elicit their responses. Descriptive statistics, Analysis of Variance (ANOVA) and Regression Model were used for the data analysis. The R value depicts that the use of information technology accounted for (76.3%) improvement in tax administration in Nigeria. The results strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Structured questionnaire was administered on the study sample of 162 (one third) based in Lagos, drawn randomly from the total population of 484 staff in the FIRS offices located in Southwest region (Adeyeye, 2019) using Taro Yamane sample size calculator technique at 5% margin of error. The data gathered was mainly through administered questionnaire which was divided into two sections; Section A is based on personal data of the respondent while section B comprises of five point Likert scale questions ranging from Strongly Agree (5), Agree (4), Undecided (3), Disagree (2), and Strongly Disagree (1).The scores of "strongly disagree" and "disagree" were taken to represent a statement not agreed upon, equivalent to mean score of 0 to 2.5.…”
Section: Methodsmentioning
confidence: 99%
“…Structured questionnaire was administered on the study sample of 162 (one third) based in Lagos, drawn randomly from the total population of 484 staff in the FIRS offices located in Southwest region (Adeyeye, 2019) using Taro Yamane sample size calculator technique at 5% margin of error. The data gathered was mainly through administered questionnaire which was divided into two sections; Section A is based on personal data of the respondent while section B comprises of five point Likert scale questions ranging from Strongly Agree (5), Agree (4), Undecided (3), Disagree (2), and Strongly Disagree (1).The scores of "strongly disagree" and "disagree" were taken to represent a statement not agreed upon, equivalent to mean score of 0 to 2.5.…”
Section: Methodsmentioning
confidence: 99%
“…In leading industries nations, information technology has been embraced and enhanced tax administration. The previous study showed that the usage of information technology contributed to an improvement in tax administration in Nigeria by 76.3% ( Adeyeye, 2019 ). The adoption of blockchain technology may significantly impact the national economy as well as the tax section in the VAT system ( Eilu, 2018 ; Fudamu et al, 2019 ; Setyowati et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In investigating the effect of risk management and organizational performance, disparate sets of studies emerge; The first category asserts a significantly positive effect, for example Anamanjia and Maina (2022), Belo (2020), Adeyeye (2019), Ermoko et al (2018 and Al-Khalifa (2016). A second set of empirical researches does not provide evidence on the direction of the relationship.…”
Section: Statement Of the Problemmentioning
confidence: 99%